Natural Fibres as Pavement Construction Materials: A Review - Mohd Jaaffar, Khairunnisa; Abdullah, Mohd Ezree (Recent Trends in Civil Engineering and Built Environment, 2024)
This paper provides a review on the natural fibres such as jute fibre, coir fibre and hemp fibre as one of the asphalt pavement mixtures. The rapid urbanization happening nowadays has increase the demand and usage of pavement over the years. With the increasement of traffic loads, the number of axels and high tyre pressure from vehicle develop various traffic-related pavement failure and distresses. However, engineers have found that natural fibres could be the newe solution to overcome this issue. In this review, it will be discussing about the suitability of natural fibres and the stance of natural fibres in asphalt pavement. In conclusion, this article review can investigate its possibility of natural fibres in asphalt pavement when it is modified.